O fantástico no espelho: mise en abyme em Murilo Rubião - Santos, Tainá de Moura (2023)
One of the identifying elements in the short stories by the brazilian writer Murilo Rubião is the presence of biblical epigraphs at the opening of his texts. It is common to reach the end of reading a short story, faced with the inexplicability of the narrated scenes, and to look for answers and help in the epigraphs that head all the narratives. However, at first sight, they do not seem to lend themselves to the role of clarifying the meanings of the main text. Thus, this research consists of investigating the epigraphs of Murilo Rubião's short stories as a formal aspect that promotes an intertextuality with the narratives they introduce. For this, we highlight the epigraphic reading based on the technique of mise en abyme (abyss structure), explored by André Gide (1869-1951) in the last decades of the 19th century, and theorized in the 70s by Lucien Dällenbach. In literature, the mise en abyme acquires notions of “work within the work”, of reflection and mirroring. The present analysis aims at a better understanding of the epigraphs used in the texts with the texts themselves, thus allowing the comprehension of the narratives to be broadened. The corpus is composed of five short stories, all with the epigraph belonging to the category of “threat”, a criterion listed by the researcher Audemaro Taranto Goulart (1995), namely: “Os comensais”, “Petúnia”, “Bárbara”, “Os dragões” and “O bloqueio”. In order to undertake a possible path of analysis of the mentioned texts, the methodological basis used privileges the studies of the mise en abyme by Lucien Dällenbach (1977) and André Gide (1893), in addition to the theories about the epigraph, by Gérard Genette (1982) Antoine Compagnon (2007), Jorge Schwartz (1981), Audemaro Taranto Goulart (1995), among others. The results obtained in the corpus analysis indicated that, more than a formal perspective that each epigraph would carry, these quotations promoted an intertextuality with the narratives that clarify and deepen aspects of the stories that they introduce.